Question

# Question 5 Which of the following equations has the sum of its roots as 3? (a) 2x2−3x+6=0 (b) −x2+3x−3=0 (c) √2x2−3√2x+1=0​​​​​​​  (d) 3x2−3x+3=0​​​​​​​

Solution

## a) Given that, 2x2−3x+6=0 On comparing with ax2 + bx + c = 0, we get a = 2, b = 3  and c = 6 Sum of the roots =−ba−−(−3)2=32 So, sum of the roots of the quadratic equation 2x2 – 3x + 6 = 0 is not 3, so it not the answer b) Given that, −x2 + 3.x – 3 = 0 On compare with ax2 + bx + c = 0, we get a = -1, b = 3 and c  = - 3 ∴ sum of the roots  =−ba=−(3)−1=3 So, sum of the roots of the quadratic equation −x2 + 3.x – 3\) is 3, so it is the answer c) Given that  √2x2−3√2x+1=0 ⇒2x2−3x+√2=0 On comparing with ax2 + bx + c = 0, we get a = 2, b = - 3  and c = √2 sum of the roots  =−ba=−(−3)2=32 so, sum o f the roots of the quadratic equation √2x2−3√2x+1=0 is not 3, so it is not the answer d) Given that, 3x2 – 3x + 3 = 0 ⇒x2−x+1=0 On comparing with ax2 + bx + c = 0  get a = 1 b = - 1 and c = 1 sum of the roots =−ba=−(−1)1=1 So, sum of  the roots of the quadratic equation 3x2 + 3 = 0 is not 3, so it is not the answer

Suggest corrections